Education transition for youth in Indonesia using a sequential logit model - Hoang, Thanh Tung (2014)
This paper explores the main determinants influencing education transition and the varying significance of each factor at each transition, with the application of the sequential logit model. A broad perspective of variables which include household income, size and structure, urban-rural divide, gendered aspects as well as societal perceptions were considered. In order to achieve that, a regression control approach followed by a sensitivity analysis for unobserved heterogeneity was used. By estimating successive models with increasing amount of unobserved heterogeneity, the change of coefficients of certain variables was observed and the accuracy of estimators was valued. In addition, this paper delves into policy interventions and measures which aim to raise enrollment rates while keeping dropout rates minimal and this could possibly bring Indonesia education progression in the near future.